Inflation and the policies’ controversy in Vietnam. - Nguyen, Ngoc Thanh Mai. (2009)
This paper aims to find out the original causes of the inflation peak period from the end of 2007 to the end of 2008 and tries to prove whether Vietnam has experienced an inflation crisis. Specifically, the effectiveness of the Government’s applied policies would be also analyzed. But firstly the reasons why inflation is risky to Vietnam’s economy which is considered instable would be explained. Moreover, a comparison between Vietnam and Thailand is concerned to induce some realistic lessons for Vietnam. After all theoretical and experiential analyses are presented, some policies would be suggested which could contribute effectively into the fight against inflation.